Desarrollo de competencias comunicativas utilizando los audios y videos en los estudiantes de 4-1 (2020)
In the present research work on communicative competence, it is observed how information technology is influencing Colombian education, giving a contribution to the transformation of its teaching methodologies, becoming a support for the classes taught by the educator, but government problems are producing a technological gap for the schoolgirl population, where the urban sector is more up-to-date than the rural one, which leads us to carry out an inquiry about how ICT influenced the learning of students in grade 4-1 of the IED Macondo, which consists of a population of 27 schoolchildren that are made up of 27% in students and 45.9% in female students who were characterized as questionnaires and their parents in a semi-structured interview with a survey, which showed the deficiencies they have in their production textual due to its low creativity in writing and spelling problems observed in writing. ura and inadequate and deficient reading that the students showed within their school activities, where strategy was promoted with literary narratives such as the story, legend and myth that were used during the lessons, made us use the qualitative model because we agreed to be of directly in the field of study with the subjects being investigated, in which action research allows the educator to be in the educational and social context of the learners, to express the questions that press the deficiencies to produce written texts and have an adequate pronunciation in reading, and therefore the group of learners that is investigated presented a dropout in their students 6.8% and educandas 6% in school, due to the inefficient methodology, in which their technological tools are used inadequately for learning, preventing students from having support to overcome their difficulties d e writing and reading, where podcasts with audios and videos can provide an alternative to current school teaching, facilitating better learning, in which the results of the activities show us that the use of podcasts creates opportunities to improve skills. Obstacles that they have in their textual production where audios and videos are the alternatives that can influence changes in learning and improve educational training in educational facilities.